Stacking Interactions and Photovoltaic Performance of Cs2AgBiBr6 Perovskite. Issue 6 (24th January 2023) - Igbari, Femi; Xu, Fa-Feng; Shao, Jiang-Yang; Ud-Din, Faraz; Siffalovic, Peter; Zhong, Yu-Wu
Abstract : Elpasolite Cs2 AgBiBr6 also known as double perovskite has been touted in recent years as a promising alternative to the lead‐based perovskite for light harvesting. Its structure and properties mainly stem from the replacement of Pb 2+ cation with a pair of aliovalent silver (Ag + ) and bismuth (Bi 3+ ) cations. Although the elpasolite Cs2 AgBiBr6 exhibits improved stability, its photophysical properties and device performance are inferior to those of the Pb‐based perovskites. To date, numerous efforts have been geared toward the development of efficient Cs2 AgBiBr6 solar cells. However, the indirect, wide bandgap and high exciton binding energy of Cs2 AgBiBr6 have limited such efforts. This has been attributed to its low (zero) electronic dimensionality (0D), formation of small polaronic states, and interfacial imperfections with charge transporting layers. In this review, the different aspects of the elpasolite Cs2 AgBiBr6 in relation to compositional and interlayer interactions in solar cell are discussed, and its suitability for photovoltaic application is assessed, accompanied by potential measures to further advance its performance. An alternate application of Cs2 AgBiBr6 in photocatalysis, which takes advantage of its less toxicity and better stability, is also discussed. Abstract : Cs2 AgBiBr6 exhibits low toxicity and better stability. However, its photophysics and device performance are significantly inferior to those of the lead‐based perovskites. Beyond its indirect and wide bandgap characteristic, compositional faults and interlayer imperfections in devices also contribute to the low performance. Efforts to mitigate these challenges are reviewed and new approaches are proposed.